INTEGRASI NILAI-NILAI AL-QUR'AN DAN HADIST DALAM PENGEMBANGAN PENDIDIKAN KARAKTER DI ERA DIGITAL - Erni Yusnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is crucial for shaping individual morals, especially for the younger generation. This article discusses the importance of incorporating Quranic and Hadith values ​​into character education, particularly in the digital era. This study investigates how Quranic values ​​can be applied in educational curricula and daily life, particularly to foster strong morality among adolescents. This study employed a descriptive qualitative approach. Furthermore, it found that character education faces challenges in the digital world, such as the spread of negative information, hoaxes, and cyberbullying. Therefore, to avoid the negative impacts of technological advancements, it is crucial to use technology cautiously and implement Islamic moral values. Amidst rapid digital development, parents, educators, and the community have a crucial role in encouraging the younger generation to uphold noble moral values.